Transcription Factor Affects Patterning of Axon migration in Caenorhabditis elegans - Aseel Raheem Al-Aamiri (Al-Qadisiyah Journal of Pure Science, 2018)
Axon navigation through nervous system development is a chalinging process. How do axons navigate to their final targets still unclear. Several axon guidance cuesresponspel for  regulating axon guidancehave been identified in the past decade. Resent studies indicate that transcription factors have a crusial role in the nervous development by coordinatiing neuron response to guidance cues. The nervous system is one of the most complex system that controls the behavior and physiology of body. Caenorhabditis elegans nervous system development involves cell migration and axon guidance. Neuronal cell body and its axon migrate along the dorsal ventral and anterior posterior axis to reach their final position to generate the final nervous system structure. UNC-53 is a cytoplasmic protein that regulates growth cone migration. The C. elegans homolog, NAV 2, a member of the Neuron Navigator protein family, also plays roles in axon guidance and outgrowth.        In this study, it was used the nematode C.elegans to study the transcriptional regulation of axon guidance, axon branching and cell position. It was found  unc-5(e53) and unc-53(n152) single mutants had less axon outgrowth defects, compared with zag-1(zd86);unc-5(e53) and zag-1(zd86);unc-53(n152) double mutants that displayed a much higher frequency of HSN axon outgrowth defects relative to wild type.